Kelimpahan Mikroplastik dalam Air Minum Isi Ulang: Efek Temperatur Perebusan - Nabilah Zafirah Azzahra; Siti Maisaroh; Budiman Budiman; Fatmawati Patang (LPPM Universitas Mataram, 2026)
Microplastic contamination in refill drinking water is a relevant public health concern because this product is widely consumed. This study analyzed the effect of boiling temperature on microplastic abundance and characteristics in refill drinking water from Samarinda City. Four samples from different refill depots were randomly collected and treated as unboiled water, water boiled at 70°C, and water boiled at 100°C. Microplastics were separated by density separation using saturated NaCl, organic matter digestion with 30% H2O2, filtration, and microscopic identification. The results showed that refill drinking water contained pellets, fragments, films, and fibers, with black particles being dominant at 58.87%. Boiling at 70°C produced the lowest microplastic abundance and reduced particles by up to 50% compared with unboiled water. In contrast, boiling at 100°C left higher abundance and generated film particles of 20 particles/L. These findings indicate that moderate-temperature boiling is more effective for reducing microplastic exposure before water consumption